Diagnóstico comunitario de salud del Barrio Pucacocha bajo sector I y II, septiembre-diciembre de 2013 - Sarango Gualán, Hilda Beatriz (2013)
This research's main objective is to help strengthen the INTEGRAL MODEL SYSTEM WARNING NATIONAL COMMUNITY FAMILY HEALTH Intercultural E at the University Hospital of Motupe, providing statistics and data that enable basic health teams-EAIS (Care Teams Integral health) formulate local health proposals, aimed at improving the quality of life of Barrio Pucacocha Sector I and II. The universe consisted of 243 families and 919 inhabitants, this research is descriptive, in which facts and characteristics related to population and environment are detailed, the instrument for data collection was the family record compiled by the MSP and an annex to this record, the interview form complemented the information, the data is also analyzed, obtaining results that will serve as a baseline. Among the most relevant data include: that the most prevalent is the female sex, level of education is outstanding Basic 11 Illiterate some of whom are heads of households were found, identified children with nutritional problems, as school teens and most of them is with good nutritional status and most studies in regard to sexually active women, the rhythm method is the most widely used family planning. Regarding the epidemiological profile include the Hypertension is the most prevalent chronic disease affecting aged between 20 and 64 years, including degenerative diseases found column Cancer, breast and uterus, diseases found impact Regarding Herpes Zoster the most outstanding intellectual disabilities is disabled. Research bibliography and appendices which involves the development of it is supported. Keywords: Community health diagnosis, Model of Integral Attention of Health.